Theoretical and Experimental Studies of CO2 Absorption in Double-Unit Flat-Plate Membrane Contactors - Ho, C.-D. (MDPI, 2022)
Theoretical predictions of carbon dioxide absorption flux were analyzed by developing one-dimensional mathematical modeling using the chemical absorption theory based on mass-transfer resistances in series. The CO2 absorption into monoethanolamine (MEA) solutions was treated as chemical absorption, accompanied by a large equilibrium constant. The experimental work of the CO2 absorption flux using MEA solution was conducted in double-unit flat-plate membrane contactors with embedded 3D turbulence promoters under various absorbent flow rates, CO2 feed flow rates, and inlet CO2 concentrations in the gas feed stream for both concurrent and countercurrent flow operations. A more compact double-unit module with embedded 3D turbulence promoters could increase the membrane stability to prevent flow-induced vibration and enhance the CO2 absorption rate by overwhelming the concentration polarization on the membrane surfaces. The measured absorption fluxes with a near pseudo-first-order reaction were in good agreement with the theoretical predictions for the CO2 absorption efficiency in aqueous MEA solutions, which was shown to be substantially larger than the physical absorption in water. By embedding 3D turbulence promoters in the MEA feed channel, the new design accomplishes a considerable CO2 absorption flux compared with an empty channel as well as the single unit module. This demonstrates the value and originality of the present study regarding the technical feasibility. The absorption flux enhancement for the double-unit module with embedded 3D turbulence promoters could provide a maximum relative increase of up to 40 due to the diminution in the concentration polarization effect. The correlated equation of the average Sherwood number was obtained numerically using the fourth RungeâKutta method in a generalized and simplified expression to calculate the mass transfer coefficient of the CO2 absorption in the double-unit flat-plate membrane contactor with turbulence promoter channels. Â© 2022 by the authors. Licensee MDPI, Basel, Switzerland.